Periprostatic Adipose Tissue Microenvironment: Metabolic and Hormonal Pathways During Prostate Cancer Progression - Sacca, Paula Alejandra; Calvo, Juan Carlos (Frontiers in Endocrinology, 2022)
Periprostatic adipose tissue (PPAT) is site of invasion of prostate cancer (PCa) and is part of the microenvironment. It was shown that PPAT secretes factors as well as fatty acids (FAs) that alter the microenvironment of the PCa. PPAT secretome of patients with PCa-T3 stage (PPAT-T3) has a metabolic profile enriched in several pathways related to energy production, indicating a greater energy requirement by the tumor, when compared to that of patients in PCa-T2 stage (PPAT-T2). PPAT-T3 also shows enrichment in pathways related to hormone response, polyamine synthesis and control of protein synthesis, through amino acid, RNA, and nucleotide metabolism. PPAT-T2 and PPAT-BPH secretome have less complex metabolic profile, both related with energy balance, while PPAT-BPH has hormone response through insulin pathway. Undoubtedly, a deeper characterization of the human PPAT will lead to a better understanding of the disease and possibly allow new stratification factors and the design of a specific therapy that targets crucial components of the tumor microenvironment as another way to treat or control the disease.